Government Budget Deficits and Interest Rates: An Empirical Analysis for Pakistan (The Pakistan Development Review, 1989)
In recent years many developed and developing countries have experienced large budget deficits, generally believed to be the result of the over-expansionary fiscal actions of the policy-makers. The prevailing orthodoxy argues that larger budget deficits cause interest rates to rise and thus leads to crowding-out of private investment expenditure. The empirical evidence on this point, however, has been inconclusive. Studies by Cebula (1988); Deleuw and Holloway (1985); Hoelscher (1986) and Khan (1988) have found evidence linking deficits to higher interest rates. On the other hand, Dewald (1983); Dwyer (1982); Evans (1985, 1987); Hoelscher (1983); Makin (1983); Mascaro and Meltzer (1983); McMillin (1986); Motley (1983) and Plosser (1982) have concluded that deficits do not have significant impact upon interest rates. In Pakistan, the overall government budget deficit as a percentage of GDP has increased steadily over time. During the Eighties, however, it increased at a much faster rate compared to the earlier periods and reached an unprecedented level of 8.4 percent in 1987-88. Since then it has declined to a little over 7 percent, but is still considered by many experts to be too high. These large deficits have led to excessive borrowing, which has resulted in a more than five-fold increase in domestic debt since 1980-81. Unfortunately, little is known about the possible effects of budgetary deficits on the performance of the economy. In this study, an attempt is made to investigate the nature of the empirical relationship that may exist between the government budget deficit and nominal interest rates in Pakistan. The findings are expected to shed light on whether budgetary deficits in Pakistan, by causing interest rates to rise, have resulted in the "crowding-out" of private consumption and investment.